Effect of Soil Management Practices on the Sweeping Operation during Coffee Harvest - Tavares, Tiago de Oliveira [UNESP]; Paula Borba, Matheus Anaan de [UNESP]; Oliveira, Bruno Rocca de [UNESP]; Silva, Rouverson Pereira da [UNESP]; Voltarelli, Murilo Aparecido; Santana Ormond, Antonio Tassio [UNESP] (Amer Soc Agronomy, 2018)
The mechanical sweeping and picking of coffee berries are necessary to recover berries that naturally fall on the soil during the mechanical harvesting process. The soil characteristics and the materials that are collected affect these two operations; in addition, there are reports that suggest that mechanical sweeping and picking are hampered by subsoiling. In this regard, the current study evaluated losses during the mechanical sweeping and picking of coffee cultivated under four soil management treatments in Presidente Olegario, MG, Brazil. The four treatments consisted of the following soil management practices: subsoiling and crushing; subsoiling and harrowing; subsoiling followed by harrowing and crushing; and the control, with no soil management. The soil was prepared in 2014, while the coffee sweeping and picking occurred in 2015 and 2016. The experimental design followed the assumptions of statistical process control, and fifteen points were evaluated per treatment in accordance with the statistical process control guidelines. The lowest loss rates were obtained for the subsoiling and crushing soil management treatment, whereas harrowing after subsoiling led to the highest losses and the lowest process quality.